WHEN YOUR HEART IS AFLUTTER AND YOU'RE WEAK AT THE KNEES: A CASE REPORT. Issue 11 (9th October 2013) - Davidson, Amy; Longman, Cheryl; Farrugia, Maria
Abstract : A 49 year old gentleman presented to Neurology with a 10 year history of deteriorating mobility. He described an evolving bilateral foot drop from his mid–thirties, with progressive symptoms affecting his left hand, manifesting as difficulties performing fine tasks such as snapping his fingers. He also had bilateral sensorineural deafness. He was known to cardiology with a tachy–brady syndrome which had evolved into persistent atrial fibrillation not requiring a pacemaker. His mother had Alzheimer's disease, with a "shuffling gait". His brother suffered from childhood polio. On examination, he was dysarthric, with wasting and weakness of the interossei and thenar eminence in both hands. There was wasting of the calf muscles and of tibialis anterior, with normal arched feet. Weakness was present at hips, knees and ankles with marked symmetrical weakness of ankle dorsiflexion bilaterally. Investigations: showed normal CK with a myopathic pattern on EMG. His ECG showed atrial fibrillation with left bundle branch block and echocardiography demonstrated biatrial enlargement. Given his presentation and family history a muscle biopsy was performed. This revealed numerous atrophic fibers and an increase in internal nucleation, with scattered cytoplasmic vacuoles. There was also a mild increase in type 1 fibre and abnormal Desmin staining. Sequencing of the VCP (valosin containing protein) gene did not identify any abnormality. Then sequencing of the DES (Desmin) gene was performed and identified a mis–sense mutation c.1346A>C (p.Lys449Thr), diagnosing a desminopathy. Desminopathy is part of the myofibrillar myopathies (MFMs). They are a group of muscular dystrophies, associated with myofibrillar disorganisation and accumulation of myofibrillar degradation products. Diagnosis is via muscle pathology and electron microscopy. Inheritance can be autosomal dominant, autosomal recessive, X–linked and rarely sporadic. Age of onset can vary between third and seventh decades. Patients present with progressive muscle weakness which can be distal, limb–girdle or scapuloperoneal in distribution. Cardiomyopathy may precede muscle weakness and cardiac arrhythmias may occur. Respiratory insufficiency, including diaphragm paralysis, peripheral neuropathy and spinal rigidity can be associated with some subsets. Desmin is a 53kDa intermediate filament which is involved in the formation of cellular cytoskeleton. Over 40 mutations have been described, the majority clustering in the alpha–helical head domain but there is also newer evidence that mutations in the "tail" region can lead to similar phenotypes. 1–4 Recognising MFMs is important because of their myriad of implications. Although there is no active treatment for the muscular dystrophy, cardiac and respiratory interventions can be used. Furthermore, it is crucial to identify family members at risk and counsel them appropriately.